Enhanced electrocatalytic performances of NiCr layered double hydroxides by oxalate intercalation in anion exchange membrane water electrolysis - Pal, Santanu; Sinha, Nibedita; Das, Chandni; Chauhan, Inderjeet; Ahmed, Tanbir; Roy, Poulomi (ACS Applied Materials & Interfaces, 2025)
Layered double hydroxides (LDHs) have attracted much attention these days in the field of water electrolysis due to easy modulation in their layered structure and properties. Herein, NiCr-LDH has been developed, and its interlayer spacing has been considerably increased by oxalate intercalation. Such increased interlayer spacing allows easy access of hydroxides to a large number of electroactive sites and thereby boosts the electrocatalytic performances both for oxygen and hydrogen evolution reactions. Being very active toward both the electrocatalytic reactions, the oxalate-intercalated NiCr-LDH was further explored in an alkaline anion exchange membrane water electrolyzer (AEMWE), achieving 800 mA cm-2 at 1.88 V cell voltage at an operating temperature of 60 degrees C. In fact, the electrolyzer efficiency has been determined to be as high as 69.66%, and the calculated H2 production cost was found to be \$0.97 per gasoline-gallon equivalent, which is well below the targeted cost by the Department of Energy, USA. The electrocatalyst was also examined in harsh alkaline media, like highly saline or seawater, which also indicated its ability to carry out sustainable seawater electrolysis, restricting chlorides to a great extent. Interestingly, post-electrolysis characterization reveals the fact that oxalate decomposition aided carbonate formation within interlayers of NiCr-LDH, and high affinity toward hydroxides is responsible for restricting chlorides during the electrolysis process, apart from the great electrocatalytic activity.
Keywords: Anion exchange; hydrogen production; interlayerspacing; Layered double hydroxide; Sustainable; water electrolyzer